Role of Sm3+ on Mn Nanoparticles Embedded Zinc Tellurite Glasses: Absorption and Luminescence Characteristic - Nurul Ainaa Najihah, Busra; Ramli, Arifin; Goshal, Sib Krishna; Rodziah, Nazlan (Trans Tech Publications, 2020)
Enhancing the optical performance of rare earth doped binary inorganic glasses is an everdemanding quest. Samarium (Sm3+) doped zinc tellurite glasses containing Manganese (Mn) nanoparticles (NPs) with composition (59-x)TeO2-20ZnCl2-10ZnO-10Li2O-1Sm2O3-(x)Mn3O4, where x = 0 to 0.06 mol% are prepared by melt quenching technique. The role played by Mn NPs in enhancing the optical behaviors are analyzed and discussed. The XRD patterns confirm the amorphous nature of the glass. The UV-Vis-NIR spectra reveal seven prominent absorption bands of Sm3+ ions. The photoluminescence spectra display four peaks corresponding to 4G5/2→6H5/2, 4G5/2 →6H7/2, 4G5/2→6H9/2 and 4G5/2 →6H11/2 transitions. An enhancement in the luminescence intensity is observed up to 0.05 mol% concentration of NPs and the intensity quenches beyond it. The enhancement is attributed to local electric field effect of NPs in the proximity of Sm3+ ion. Our results on improved optical response via precise control of NPs contents may be useful for the development of solid state lasers and amplifiers.